Development of Heat Transfer Learning Media Based on Android Application Inventor (AI) to Instill Student Self Directed Learning (Journal of Innovative Science Education, 2017)
This study aims to develop a learning media of heat transfer based on android Application Inventor (AI) to instill student self directed learning. This research is designed with research and development design, adapted from modified 3D model whichstages includes define, design and development. The subject of this research is the students of PGSD (Primary School Teacher Education) Study Program of Universitas PGRI Semarang. The result of validation by expert on instructional learning media of heat transfer based on android Application Inventor (AI) get 3.76 values is categorized as very feasible, the presentation of the content obtained value 3.84 with very decent category. Students responded positively to the learning media of heat transfer based on android Application Inventor (AI) developed. Based on the result of data analysis, it can be concluded that learning media of heat transfer based on android Application Inventor (AI) is very feasible, effective, and got positive response with 88.56% percentage by students and can be used as one learning resource that can increase student self directed learning. Penelitian ini bertujuan untuk mengembangkanmedia pembelajaran perambatan kalor berbasis android Application Inventor (AI) untuk menanamkan kemandirian belajar mahasiswa. Penelitian ini dirancang dengan desain research and development, yang diadaptasi dari model 3D termodifikasi yang meliputi tahapan define, design, development. Subjek penelitian ini yaitu mahasiswa Program Studi PGSD Universitas PGRI Semarang. Hasil validasi oleh ahliterhadap media pembelajaran perambatan kalor berbasis android Application Inventor (AI) memperoleh nilai 3,76 dikategorikan sangat layak, penyajian isi memperoleh nilai 3,84dengan kategori sangat layak. Siswa memberikan respon positif terhadap media pembelajaran perambatan kalor berbasis android Application Inventor (AI) yang dikembangkan. Berdasarkan hasil analisis data dapat disimpulkan media pembelajaran perambatan kalor berbasis android Application Inventor (AI) dinyatakan sangat layak, efektif, dan mendapat respon positif dengan persentasi 88,56% oleh mahasiswa dan dapat digunakan sebagai salah satu sumber belajar yang mampu meningkatkan kemandirian belajar mahasiswa.